Troubleshooting Postintubation Hypoxia: A Simulation Case for Emergency Medicine Residents - Xiao Chi Zhang; Antoinette Golden; David Lindquist (Association of American Medical Colleges, 2016)
Abstract Introduction Opiate overdose is a dangerous but common chief complaint to the emergency department. While many patients with opiate intoxication respond well to opiate reversal agents and noninvasive airway management, some cases involve persistent respiratory failure, hemodynamic instability, and unintentional head trauma that may necessitate airway management. This simulation allows emergency medicine residents to explore an unusual but high-risk disease process: persistent hypoxia in an intubated patient with severe acute respiratory disease syndrome (ARDS) requiring extracorporeal membrane oxygenation (ECMO). Methods This case ran for four separate iterations at a simulation center, with a Laerdal 3G Sim Man, respiratory therapist, actor, residents, and attending physician acting as specific confederates for their respective roles. Following each case, learners were debriefed at bedside, discussed a PowerPoint presentation, and underwent a question-and-answer session. Results Both junior and senior resident groups recognized esophageal intubation, diagnosed ARDS, and proposed treatment goals. Although junior residents recognized that optimal ventilation had not been achieved, they were unable to specifically direct ventilator recruitment maneuvers. Senior residents were more likely to articulate treatment orders, to instruct junior residents to address family members, and to recognize severe ARDS requiring early consultation of the intensive care unit and discussion of disposition. After case completion and debriefing, all learners demonstrated achievement of learning objectives, as well as managing acute dyspnea, treating opiate overdoses, and understanding the role of ECMO in severe ARDS patients. Discussion Overall, we noted this case worked well for junior EM residents with senior resident backup for supervision and guidance. The presence of a certified respiratory therapist was invaluable and was greatly appreciated by both learner groups, especially during the debriefing section where they discussed various ventilator optimization techniques in conjunction with case instructors.